4 - Thoughts on Intellectual and Institutional Links Between African and Black Studies - Murunga, Godwin R. (Africa Development, 2008)
Black identity and nationalism in the civil rights era were forged through trans- Atlantic and Pan-African solidarity. Both African and African-American intel- lectuals and institutions played key roles in Pan-African nationalism and the sustenance of civil rights struggles across the Atlantic. However, in the 1970s onwards, these Pan-African links were subverted by vertical dialogues between western, especially white, ‘experts’ of Africa and Africans; a dialogue that was skewed in favour of Africanist paradigms and knowledge because of the obvi- ous unequal distribution of intellectual resources in favour of white researchers in the global North. This shift was also matched by the preponderance of nega- tive themes about Africa, an increasing amount of ignorance in the west of the realities in Africa and the treatment of Africa as a mere object of curiosity and theory testing. This paper locates the growing ‘ignorance’ of African realities among African-Americans in the rise and dominance of Africanist Africa, its disengagement from Black Studies, the marginalisation of African-American and African scholarship (conducted by black scholars) in Euro-American scholar- ship and the de-emphasis of radical and Black intellectual traditions in the main- stream study of Africans. The paper proposes the enhancement of direct hori- zontal dialogue between Africans and African-Americans instead of the vertical dialogue between Africans and Africanists which has failed to provide an objec- tive presentation of Africa’s achievements and failures, gains and losses. Godwin Rapando Murunga, Kenyatta University, Nairobi, Kenya.